FIRST REPORT OF TEMNOCEPHALA PEREIRAI (PLATYHELMINTHES, TEMNOCEPHALIDAE) ON TRACHEMYS DORBIGNI (EMYDIDAE) FROM SOUTHERN BRAZIL –A COMPLETE MORPHOLOGICAL STUDY - A. Seixas, Samantha (2014)
Specimens and eggs of Temnocephala pereirai Volonterio, 2010 found on Trachemys dorbigni (Duméril & Bibron, 1835), were reported for the first time extending the known geographical distribution of T. pereirai from Uruguay to southern Brazil. Sixteen turtles were collected from a dam at 'Centro Agropecuário da Palma', Universidade Federal de Pelotas (UFPel), Municipality of Capão do Leão, State of Rio Grande do Sul, Brazil. The helminthes were fixed according to our standard protocols. Juvenile and adult temnocephalans were translucent and without the red-eye pigmentation. The worms were living in the inner corners of the plastron, near the legs, together with the eggs, and in the center of the plastron. Eggs were elongated, thick-shelled, with a small and subpolar filament. The most distinctive features of this species were: 1. cirrus's introvert proximal portion with spines from top to mid-level, followed by a smooth region, extending to the introvert proximal limit; 2. vagina with strong muscular walls and a single, symmetrical sphincter; 3. vesicula intermedia unusually long; 4. small dorsolateral 'excretory' syncytial epidermal plates larger in the anterior portion; and 5. excretory pore in the anterior portion of the plate, near the internal limit. The specimens in the present work had larger body length and base diameter of the shaft than the Uruguayan specimens. Keywords: freshwater turtles - Neotropic